Tilapia (Oreochromis niloticus) Farming In Buckets In Sakatiga Village, Indralaya District, Ogan Ilir Regency - Edo Saputra; Retno Cahya Mukti; Mohamad Amin; Dade Jubaedah; Yulisman Yulisman; Madyasta Anggana Rarassari (Department of Aquaculture, 2022)
Currently, the problem of increasingly limited land availability has led to increasingly limited cultivation activities. The decreasing number of large cultivation locations requires people to be more creative in utilizing narrow locations and in saving water. Fish farming in buckets is a potential solution for aquaculture in a narrow area with more efficient use of water, easy for the community to do in their respective homes with relatively small capital, and finally able to meet the nutritional needs of the community. The purpose of this study was to determine the growth of tilapia (Oreochromis niloticus) kept in buckets using water spinach plants (Ipomoea aquatica). This research used two treatments, namely P0: control (fish farming in buckets without using plants) and P1: fish farming in buckets using plants. Parameters observed were absolute weight growth, absolute length growth, feed efficiency, and survival. The results showed that the P1 treatment resulted in an absolute weight growth of 3.44 g, an absolute length growth of 1.12 cm, feed efficiency of 93.08%, and survival of 100%. While the P0 treatment resulted in absolute weight growth of 3.92 g, absolute length growth of 1.21 cm, feed efficiency 81.75 %, and survival of 82.5%. Rearing tilapia in buckets without water spinach plants better results than using water spinach plants.